Intracorporeal Versus Extracorporeal Anastomosis for Laparoscopic Resection of the Splenic Flexure Colon Cancer: A Multicenter Propensity Score Analysis. Issue 6 (December 2019) - Grieco, Michele; Cassini, Diletta; Spoletini, Domenico; Soligo, Enrica; Grattarola, Emanuela; Baldazzi, Gianandrea; Testa, Silvio; Carlini, Massimo
Abstract : Purpose: The aim of this study is to compare the short and long-term outcomes of intracorporeal anastomosis (IA) versus extracorporeal anastomosis (EA) during laparoscopic resection of splenic flexure for cancer, in 3 high-volume Italian centers. Materials and Methods: A retrospective analysis was conducted on a multicenter database of a consecutive series of patients who underwent an elective laparoscopic resection of the splenic flexure for colon cancer in 3 high-volume centers between January 2008 and August 2017. Propensity score matching analysis was performed to overcome patients' selection bias between the 2 surgical techniques. Data on patients' demographics, operative details, short-term and long-term outcomes were prospectively recorded. Results: In total, 102 patients were selected. After propensity score match, 72 patients were compared: 36 for the IA group, 36 for the EA group. The IA group showed a significantly shorter median time to first flatus, time to first stool, time to oral feeding, and time to discharge, as well as significantly lower incidence of postoperative severe surgical complications, especially in terms of wound infections, and of incisional hernia (IH). Risk factors for IH on logistic regression were longer operative time, EA, longer incision, postoperative blood transfusions, and longer specimen. Conclusions: The IA in laparoscopic resection of the splenic flexure is feasible and safe in terms of short-term and long-term outcomes. Major advantages are shorter time to first flatus and first stool, complete oral feeding and time to discharge, with minor incidence of severe surgical complications, such as wound infection, and lower incidence of IH.